Relationship between spiritual/religious beliefs and spiritual well-being of the nursing team - Lívia Helena Pereira da Silva; Ramon Moraes Penha; Maria Júlia Paes da Silva (Rev Rene)
This exploratory quantitative study aimed at verifying the relationship between spiritual/religious beliefs and spiritual well-being of the Nursing team at HU/USP and describes whether there are significant differences between their sectors. The following tools were applied: Durel and EBEE in 118 individuals. It was shown that 93.2% (n=110) of the participants reported to belong to a religion and 55.9% (n=66) practice a daily individual religious activity. In EBEE, 83.4% (n=98) of the participants had an average of 32.28 (sd = 10.958), considered low. For the subscales of Existential Well-Being, 76.7% (n=90) of participants had an average of 15.5 and for the Religious Well-Being 78.3% (n=92) maintained an average of 14.5, also considered low. There was no variation between sectors surveyed. In conclusion, this study serves as a warning to the spiritual stress suffered by these professionals in the hospital. There are also limitations, once there are no similar studies that could provide evidence to compare the result analyses.